Method and device for determining preparation parameters by using TOPSIS-based concrete self-healing performance evaluation technology, medium and product
Through the concrete self-healing performance evaluation technology based on TOPSIS, the difference between the internal and surface healing of concrete is comprehensively considered and the target preparation parameters are determined, which solves the problem that traditional methods cannot comprehensively evaluate the self-healing performance of concrete and improves the overall level of concrete self-healing performance.
Patent Information
- Application Number
- CN202411845802.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-13
AI Technical Summary
Traditional methods cannot comprehensively evaluate the self-healing properties of concrete, especially the differences and correlations between internal and surface healing and their impact on overall performance, resulting in poor self-healing properties of prepared concrete.
The concrete self-healing performance evaluation technology based on TOPSIS was adopted, and multiple groups of sample groups were prepared and performance tests were performed to obtain the normalized water absorption change degree, crack width change degree and strength recovery degree, and the water absorption recovery weight and crack width healing weight were determined. The similarity coefficient was determined by TOPSIS comprehensive analysis method, thereby determining the target preparation parameters.
A comprehensive evaluation of concrete self-healing performance has been achieved, and the self-healing performance of prepared concrete has been improved, and the self-healing performance can be characterized more accurately. The closer the similarity coefficient is to 1, the better the self-healing performance.
Smart Images

Figure CN119738312A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of self-healing recovery analysis, and in particular to a method, device, medium and product for determining preparation parameters using TOPSIS-based concrete self-healing performance evaluation technology. Background Art
[0002] In terms of evaluating the self-healing performance of concrete, traditional evaluation methods include surface crack width healing degree evaluation, water absorption and permeability change degree evaluation, ultrasonic testing and CT scanning analysis. These methods have different focuses. For example, the surface crack width healing degree evaluation method regularly measures the width change degree of concrete surface cracks to judge its self-healing effect. This method is simple and intuitive, and is also the most widely used method in current research and engineering practice. The degree of change in water absorption and permeability is to judge the degree of closure of the micro-crack pores inside the concrete by measuring the amount of water absorbed by the concrete in a fixed time before and after self-healing, or the amount of time required for a certain amount of water to pass through. The common characterization parameter unit is g / s 0.5 . Ultrasonic testing is based on the correlation between the propagation speed of ultrasound in concrete and the compressive strength. The strength and internal defects of concrete are determined by analyzing acoustic parameters. The unit of wave velocity, a common characterization parameter, is m / s. Ultrasonic waves propagate quickly in intact concrete structures. In unclosed internal defects such as cracks and pores, the reflection and refraction of sound waves will occur due to the sudden change of the medium interface, thereby reducing the propagation speed of ultrasound. Based on this, the comparative analysis of the wave velocity can roughly determine the internal healing of concrete. CT scanning analysis can provide overall information of the concrete structure through three-dimensional reconstruction of images, including a digital model of its internal pores, cracks and surface defects. According to the statistical algorithm, the degree of internal structural changes of concrete before and after self-healing can be accurately obtained, and the details of the structural changes before and after self-healing can also be intuitively compared and analyzed through the reconstructed model image.
[0003] However, although the evaluation method of surface crack width healing degree test is the simplest and most intuitive and widely used, it can only focus on the surface healing situation and cannot deeply reflect the healing effect inside the concrete. The water absorption and permeability change evaluation method can judge the internal pore and crack situation of concrete according to the difficulty of the pore water movement path, thereby comparing and reflecting the healing effect of concrete before and after, but it ignores the healing situation of the open pores and cracks on the surface of concrete. Although ultrasonic testing can also reflect the healing situation of pores and cracks inside concrete, the ultrasonic reflection and refraction path it is based on is based on the shortest distance short-range straight line segment, which cannot reflect the complete internal pore and crack situation, and cannot reflect the healing situation of the concrete surface. Although CT scanning can provide more detailed and comprehensive information on the internal and external structures of concrete through three-dimensional reconstruction, its operation is complicated, the cost is high, and there are certain requirements for the test conditions of the concrete test object, which greatly limits its application in engineering practice.
[0004] In summary, traditional methods cannot comprehensively evaluate the self-healing properties of concrete, especially they fail to comprehensively consider the differences and correlations between internal and surface healing in the concrete self-healing process and their impact on the overall performance, resulting in poor self-healing properties of the prepared concrete. Summary of the invention
[0005] The purpose of this application is to provide a method, device, medium and product for determining preparation parameters using TOPSIS-based concrete self-healing performance evaluation technology, so as to solve the problem that the self-healing performance of concrete cannot be fully evaluated and the self-healing property of the prepared concrete is poor.
[0006] To achieve the above objectives, this application provides the following solutions:
[0007] In a first aspect, the present application provides a method for determining preparation parameters using a TOPSIS-based concrete self-healing performance evaluation technology, comprising:
[0008] Prepare multiple groups of sample groups; the sample groups include: prefabricated cracked concrete samples and non-prefabricated cracked concrete samples; the prefabricated cracked concrete samples are concrete samples with cracks, and the non-prefabricated cracked concrete samples are concrete samples without cracks; the preparation parameters of the concrete samples in different groups of sample groups are different, and the preparation parameters of the prefabricated cracked concrete samples and the non-prefabricated cracked concrete samples in the same group are the same; the preparation parameters include: the types of materials constituting the concrete samples and the mix ratio of the materials;
[0009] Performing performance tests on each of the sample groups respectively, and obtaining the normalized water absorption rate change degree, the normalized crack width change degree, and the normalized strength recovery degree of each of the sample groups;
[0010] Based on the normalized water absorption change degree, the normalized crack width change degree and the normalized strength recovery degree of all sample groups, the water absorption recovery weight and the crack width healing weight are determined;
[0011] Determine the weighted water absorption change degree of each sample group based on the normalized water absorption change degree of each sample group and the water absorption recovery weight, and determine the weighted crack width change degree of each sample group based on the normalized crack width change degree of each sample group and the crack width healing weight;
[0012] Using the TOPSIS comprehensive analysis method, based on the weighted water absorption rate change degree and the weighted crack width change degree of all sample groups, the similarity coefficient of each sample group is determined; the similarity coefficient is used to characterize the self-healing performance;
[0013] The preparation parameters of the sample group with the largest similarity coefficient are determined as target parameters, and the target parameters are determined as preparation parameters when producing concrete.
[0014] Optionally, a performance test is performed on each sample group, and a normalized water absorption rate change degree, a normalized crack width change degree, and a normalized strength recovery degree of each sample group are obtained, including:
[0015] The precast cracked concrete specimens in each specimen group are respectively subjected to performance tests. During the performance tests, the performance parameters of each precast cracked concrete specimen are collected. The performance parameters of the precast cracked concrete specimens include: a first load, a first crack width, a first water absorption rate, a second crack width, a second water absorption rate, and a second load.
[0016] The non-prefabricated cracked concrete samples in each sample group are respectively subjected to performance tests. During the performance tests, the performance parameters of each non-prefabricated cracked concrete sample are collected. The performance parameters of the non-prefabricated cracked concrete sample include: the third water absorption rate and the fourth water absorption rate;
[0017] Calculating the change degree of the original water absorption of each sample group according to the first water absorption, the second water absorption, the third water absorption and the fourth water absorption in each sample group, and performing maximum and minimum normalization processing on the change degree of the original water absorption of each sample group to obtain the normalized change degree of water absorption of each sample group;
[0018] Calculating the change degree of the original crack width of each sample group according to the first crack width and the second crack width in each sample group, and performing maximum and minimum normalization processing on the change degree of the original crack width of each sample group to obtain the normalized change degree of the crack width of each sample group;
[0019] The original strength recovery degree of each sample group is calculated according to the first load and the second load in each sample group respectively, and the original strength recovery degree of each sample group is subjected to maximum and minimum normalization processing to obtain the normalized strength recovery degree of each sample group.
[0020] Optionally, the calculation formula for the degree of change of the original water absorption rate includes:
[0021] Δw=(w 1 -w 2 )-(w 3 -w 4 );
[0022] Among them, Δw is the change degree of original water absorption; w 1 is the first water absorption rate; w 2 is the second water absorption rate; w 3 is the third water absorption rate; w 4 It is the fourth water absorption rate.
[0023] Optionally, the calculation formula for the degree of change of the original crack width includes:
[0024]
[0025] Among them, Δc is the change degree of the original crack width; c 1 is the first crack width; c 2 is the second crack width.
[0026] Optionally, based on the normalized water absorption change degree, the normalized crack width change degree and the normalized strength recovery degree of all sample groups, the water absorption recovery weight and the crack width healing weight are determined, including:
[0027] Based on the normalized water absorption change degree and the normalized strength recovery degree of all sample groups, the correlation coefficient between the water absorption change degree and the strength recovery degree is calculated to obtain the water absorption recovery correlation coefficient;
[0028] Based on the normalized crack width change degree and the normalized strength recovery degree of all sample groups, the correlation coefficient between the crack width change degree and the strength recovery degree is calculated to obtain the crack width healing correlation coefficient;
[0029] Based on the water absorption recovery correlation coefficient and the crack width healing correlation coefficient, the water absorption recovery weight and the crack width healing weight are calculated.
[0030] Optionally, the TOPSIS comprehensive analysis method is used to determine the similarity coefficient of each sample group based on the weighted water absorption rate change degree and the weighted crack width change degree of all sample groups, including:
[0031] The maximum value among all weighted water absorption rate changes is determined as the positive ideal solution of water absorption rate, the minimum value among all weighted water absorption rate changes is determined as the negative ideal solution of water absorption rate, the maximum value among all weighted crack width changes is determined as the positive ideal solution of crack width, and the minimum value among all weighted crack width changes is determined as the negative ideal solution of crack width;
[0032] The similarity coefficient of each sample group is determined according to the weighted water absorption change degree and the weighted crack width change degree of each sample group and the positive ideal solution of water absorption, the negative ideal solution of water absorption, the positive ideal solution of crack width and the negative ideal solution of crack width.
[0033] Optionally, the similarity coefficient of each sample group is determined according to the weighted water absorption change degree and the weighted crack width change degree of each sample group and the positive ideal solution of water absorption, the negative ideal solution of water absorption, the positive ideal solution of crack width and the negative ideal solution of crack width, including:
[0034] Determine any sample group as the current sample group;
[0035] Calculating the positive ideal distance of the current sample group according to the positive ideal solution of water absorption, the positive ideal solution of crack width, and the weighted degree of change of water absorption and the weighted degree of change of crack width of the current sample group;
[0036] Calculating the negative ideal distance of the current sample group according to the negative ideal solution of water absorption, the negative ideal solution of crack width, and the weighted degree of change of water absorption and the weighted degree of change of crack width of the current sample group;
[0037] The similarity coefficient of the current sample group is calculated according to the positive ideal distance and the negative ideal distance of the current sample group.
[0038] In a second aspect, the present application provides a computer device, comprising: a memory, a processor, and a computer program stored in the memory and executable on the processor, wherein the processor executes the computer program to implement any of the above-described methods for determining preparation parameters using TOPSIS-based concrete self-healing performance evaluation technology.
[0039] In a third aspect, the present application provides a computer-readable storage medium having a computer program stored thereon, which, when executed by a processor, implements any of the above-mentioned methods for determining preparation parameters using TOPSIS-based concrete self-healing performance evaluation technology.
[0040] In a fourth aspect, the present application provides a computer program product, including a computer program, which, when executed by a processor, implements any of the above-mentioned methods for determining preparation parameters using the TOPSIS-based concrete self-healing performance evaluation technology.
[0041] According to the specific embodiments provided in this application, this application discloses the following technical effects:
[0042] The present application discloses a method, device, medium and product for determining preparation parameters by using TOPSIS-based concrete self-healing performance evaluation technology. First, multiple groups of sample groups are prepared; then, performance tests are performed on each sample group respectively, and the normalized water absorption rate change degree, normalized crack width change degree and normalized strength recovery degree of each sample group are obtained; secondly, based on the normalized water absorption rate change degree, normalized crack width change degree and normalized strength recovery degree of all sample groups, the water absorption rate recovery weight and the crack width healing weight are determined; then, based on each sample group respectively, the water absorption rate recovery weight and the crack width healing weight are determined; The normalized water absorption change degree and water absorption recovery weight of each sample group are used to determine the weighted water absorption change degree of each sample group, and the weighted crack width change degree of each sample group is determined based on the normalized crack width change degree and crack width healing weight of each sample group; again, the TOPSIS comprehensive analysis method is used to determine the similarity coefficient of each sample group based on the weighted water absorption change degree and the weighted crack width change degree of all sample groups; finally, the preparation parameters of the sample group with the largest similarity coefficient are determined as the target parameters, and the target parameters are determined as the preparation parameters for concrete production. The similarity coefficient determined by the TOPSIS comprehensive analysis method in this application can be used to characterize the self-healing performance. The closer the similarity coefficient is to 1, the greater the self-healing performance is, which realizes a comprehensive evaluation of the self-healing performance of concrete and improves the self-healing performance of the prepared concrete. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] In order to more clearly illustrate the technical solutions in the embodiments of the present application or related technologies, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0044] Figure 1 A schematic flow chart of a method for determining preparation parameters using a TOPSIS-based concrete self-healing performance evaluation technology provided in one embodiment of the present application;
[0045] Figure 2 It is a schematic diagram of the results of the normalized water absorption rate change, the normalized crack width change and the normalized strength recovery degree;
[0046] Figure 3 is the correlation coefficient heat map;
[0047] Figure 4 Schematic diagram of the difference between TOPSIS and strength recovery;
[0048] Figure 5 A schematic diagram of the structure of a computer device provided in one embodiment of the present application. DETAILED DESCRIPTION
[0049] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0050] The purpose of this application is to provide a method, device, medium and product for determining preparation parameters using TOPSIS-based concrete self-healing performance evaluation technology, aiming to achieve a comprehensive evaluation of concrete self-healing performance.
[0051] In order to make the above-mentioned objects, features and advantages of the present application more obvious and easy to understand, the present application is further described in detail below in conjunction with the accompanying drawings and specific implementation methods.
[0052] In an exemplary embodiment, Figure 1 As shown, a method for determining preparation parameters using a TOPSIS-based concrete self-healing performance evaluation technology is provided, including:
[0053] Step 1: Prepare multiple test sample groups.
[0054] The sample groups include: prefabricated cracked concrete samples and non-prefabricated cracked concrete samples. Prefabricated cracked concrete samples are concrete samples with cracks, and non-prefabricated cracked concrete samples are concrete samples without cracks; the preparation parameters of concrete samples in different sample groups are different, and the preparation parameters of prefabricated cracked concrete samples and non-prefabricated cracked concrete samples in the same group are the same; the preparation parameters include: the types of materials constituting the concrete samples and the mix ratio of the materials.
[0055] Step 2: Perform performance tests on each sample group respectively, and obtain the normalized water absorption rate change, normalized crack width change and normalized strength recovery of each sample group.
[0056] As an optional implementation, step 2 includes:
[0057] Step 21: Perform performance tests on the precast cracked concrete specimens in each specimen group respectively. During the performance test, collect performance parameters of each precast cracked concrete specimen; the performance parameters of the precast cracked concrete specimen include: first load, first crack width, first water absorption rate, second crack width, second water absorption rate and second load.
[0058] Specifically, a performance test is performed on any prefabricated cracked concrete specimen. During the performance test, performance parameters of the prefabricated cracked concrete specimen are collected, including:
[0059] Step 211: collecting the load of a uniaxial hydraulic press for preparing a prefabricated cracked concrete sample to obtain a first load; collecting the initial crack width of the prefabricated cracked concrete sample after preparation to obtain a first crack width.
[0060] Step 212: Perform the first water absorption performance test on the precast cracked concrete sample, and regularly weigh and record the mass change of the precast cracked concrete sample after water absorption, with the unit accurate to 0.01g. After obtaining the mass change, convert the mass into water absorption height according to the equivalent cross-sectional area of the precast cracked concrete sample, and finally calculate the water absorption height and time s. 0.5 The ratio of represents the water absorption rate during the period, and the first water absorption rate is obtained.
[0061] Step 213: Waiting within a set period to allow the crack of the prefabricated cracked concrete sample to automatically become smaller, and collecting the crack width after the set period to obtain a second crack width.
[0062] Step 214: performing a second water absorption performance test on the prefabricated cracked concrete sample, and collecting the water absorption rate during the second water absorption performance test to obtain a second water absorption rate.
[0063] Step 215: Use a uniaxial hydraulic press to load the prefabricated cracked concrete specimen at a suitable speed to expand the crack width to a preset target width greater than the previous first crack width, collect the load of the uniaxial hydraulic press when the crack width reaches the preset target width, and obtain a second load.
[0064] Step 22: Performing performance tests on the non-prefabricated cracked concrete samples in each sample group, respectively. During the performance test, performance parameters of each non-prefabricated cracked concrete sample are collected; the performance parameters of the non-prefabricated cracked concrete sample include: a third water absorption rate and a fourth water absorption rate.
[0065] Specifically, a performance test is performed on any non-prefabricated cracked concrete sample. During the performance test, performance parameters of the non-prefabricated cracked concrete sample are collected, including:
[0066] Step 221: performing a first water absorption performance test on the non-prefabricated cracked concrete sample, and collecting the water absorption rate during the first water absorption performance test to obtain a third water absorption rate.
[0067] Step 222: After the first water absorption performance test of the non-prefabricated cracked concrete sample is completed, it is taken out of the water, and after waiting for a set period, a second water absorption performance test is performed on the non-prefabricated cracked concrete sample, and the water absorption rate during the second water absorption performance test is collected to obtain a fourth water absorption rate.
[0068] Step 23: Calculate the original water absorption change degree of each sample group according to the first water absorption rate, the second water absorption rate, the third water absorption rate and the fourth water absorption rate in each sample group, and perform maximum and minimum normalization processing on the original water absorption change degree of each sample group to obtain the normalized water absorption change degree of each sample group.
[0069] As an optional implementation, the calculation formula for the change degree of the original water absorption rate includes:
[0070] Δw=(w 1 -w 2 )-(w 3 -w 4 ).
[0071] Among them, Δw is the change degree of original water absorption; w 1 is the first water absorption rate; w 2 is the second water absorption rate; w 3 is the third water absorption rate; w 4 It is the fourth water absorption rate.
[0072] Step 24: Calculate the original crack width change degree of each sample group according to the first crack width and the second crack width in each sample group, and perform maximum and minimum normalization processing on the original crack width change degree of each sample group to obtain the normalized crack width change degree of each sample group.
[0073] As an optional implementation, the calculation formula for the degree of change of the original crack width includes:
[0074]
[0075] Among them, Δc is the change degree of the original crack width; c 1 is the first crack width; c 2 is the second crack width.
[0076] Step 25: Calculate the original strength recovery degree of each sample group according to the first load and the second load in each sample group respectively, and perform maximum and minimum normalization processing on the original strength recovery degree of each sample group to obtain the normalized strength recovery degree of each sample group.
[0077] Specifically, the calculation formula for the degree of recovery of the original strength includes:
[0078]
[0079] Among them, Δs is the degree of recovery of the original strength; s 1 is the first load; s 2 is the second load.
[0080] Step 3: Determine the water absorption recovery weight and the crack width healing weight based on the normalized water absorption change degree, the normalized crack width change degree and the normalized strength recovery degree of all sample groups.
[0081] As an optional implementation, step 3 includes:
[0082] Step 31: Based on the normalized water absorption change degree and the normalized strength recovery degree of all sample groups, the correlation coefficient between the water absorption change degree and the strength recovery degree is calculated to obtain the water absorption recovery correlation coefficient.
[0083] Specifically, the calculation formula of the water absorption recovery correlation coefficient includes:
[0084]
[0085] Among them, r w is the water absorption recovery correlation coefficient; n is the total number of sample groups; W i (c) is the normalized water absorption change of the i-th sample group; is the average value of the normalized water absorption change of all sample groups; S i (c) is the normalized strength recovery degree of the i-th group of samples; is the mean of the normalized strength recovery degree of all sample groups.
[0086] Step 32: Based on the normalized crack width change degree and the normalized strength recovery degree of all sample groups, the correlation coefficient between the crack width change degree and the strength recovery degree is calculated to obtain the crack width healing correlation coefficient.
[0087] Specifically, the calculation formula of the crack width healing correlation coefficient includes:
[0088]
[0089] Among them, r c is the crack width healing correlation coefficient; C i (c) is the normalized crack width variation of the i-th group of specimens; is the mean of the normalized crack width variation of all sample groups.
[0090] Step 33: Based on the water absorption recovery correlation coefficient and the crack width healing correlation coefficient, calculate the water absorption recovery weight and the crack width healing weight.
[0091] Specifically, the calculation formula for the water absorption recovery weight includes:
[0092]
[0093] Among them, α is the water absorption recovery weight; |r w | for r w The absolute value of |r c | is the absolute value of .
[0094] The calculation formula of the crack width healing weight includes:
[0095]
[0096] Among them, β is the crack width healing weight.
[0097] Step 4: Determine the weighted water absorption change degree of each sample group based on the normalized water absorption change degree and water absorption recovery weight of each sample group, and determine the weighted crack width change degree of each sample group based on the normalized crack width change degree and crack width healing weight of each sample group.
[0098] Specifically, the calculation formula for the weighted water absorption change degree includes:
[0099] v wi =α·W i (c).
[0100] Among them, v wi is the weighted water absorption change of the i-th group of samples.
[0101] The calculation formula for the weighted crack width change degree includes:
[0102] v ci =β·C i (c).
[0103] Among them, v ci is the weighted crack width change of the i-th group of samples.
[0104] Step 5: Using the TOPSIS comprehensive analysis method, the similarity coefficient of each sample group is determined based on the weighted water absorption rate change degree and the weighted crack width change degree of all sample groups; the similarity coefficient is used to characterize the self-healing performance.
[0105] As an optional implementation, step 5 includes:
[0106] Step 51: Determine the maximum value among all weighted water absorption rate changes as the positive ideal solution of water absorption, determine the minimum value among all weighted water absorption rate changes as the negative ideal solution of water absorption, determine the maximum value among all weighted crack width changes as the positive ideal solution of crack width, and determine the minimum value among all weighted crack width changes as the negative ideal solution of crack width.
[0107] Step 52: Determine the similarity coefficient of each sample group according to the weighted water absorption change degree and the weighted crack width change degree of each sample group, as well as the positive ideal solution of water absorption, the negative ideal solution of water absorption, the positive ideal solution of crack width and the negative ideal solution of crack width.
[0108] As an optional implementation, step 52 includes:
[0109] Step 521: Determine any sample group as the current sample group.
[0110] Step 522: Calculate the positive ideal distance of the current sample group according to the positive ideal solution of water absorption, the positive ideal solution of crack width, and the weighted degree of change of water absorption and the weighted degree of change of crack width of the current sample group.
[0111] Specifically, the calculation formula for the positive ideal distance includes:
[0112]
[0113] in, is the positive ideal distance of the i-th group of samples; v wmax is the ideal solution for water absorption; v cmax is the ideal solution for the crack width.
[0114] Step 523: Calculate the negative ideal distance of the current sample group according to the negative ideal solution of water absorption, the negative ideal solution of crack width, and the weighted degree of change of water absorption and the weighted degree of change of crack width of the current sample group.
[0115] Specifically, the calculation formula of the negative ideal distance includes:
[0116]
[0117] in, is the negative ideal distance of the i-th group of samples; v wmin is the negative ideal solution of water absorption; v cmin is the negative ideal solution for the crack width.
[0118] Step 524: Calculate the similarity coefficient of the current sample group according to the positive ideal distance and the negative ideal distance of the current sample group.
[0119] Specifically, the calculation formula of the similarity coefficient includes:
[0120]
[0121] Among them, F i is the similarity coefficient of the i-th sample group.
[0122] Step 6: Determine the preparation parameters of the sample group with the largest similarity coefficient as the target parameters, and determine the target parameters as the preparation parameters when producing concrete.
[0123] After step 6, the Bland-Altman analysis method was used to evaluate the consistency between the similarity coefficients of each sample group and the normalized strength recovery degree, thereby verifying the accuracy of the method for determining the preparation parameters using the TOPSIS-based concrete self-healing performance evaluation technology.
[0124] In the Bland-Altman analysis, the average value of the data pair is used to represent the general trend of the two data sets, and the difference reflects the deviation between the two data sets. In the form of a scatter plot, the average value of the data pair consisting of the similarity coefficient of each sample group and the normalized strength recovery degree is plotted on the x-axis, and the difference is plotted on the y-axis. The consistency limit is set to determine whether the difference is within a reasonable range. The upper and lower limits are determined by the following formula:
[0125]
[0126] d i =F i -S i (c).
[0127] in, is the mean of the difference between the similarity coefficient of all sample groups and the normalized strength recovery degree; σ d is the standard deviation of the difference between the similarity coefficient of all sample groups and the normalized intensity recovery degree; d i is the difference between the similarity coefficient of the i-th group of samples and the normalized strength recovery degree.
[0128] Through data analysis of the calculation results, if most of the different data points are between the consistency limits (upper and lower limits), it means that there is a good consistency between the similarity coefficients of each sample group and the normalized strength recovery degree. If there are many data points exceeding the consistency limits, it means that there is a significant deviation between the similarity coefficients of each sample group and the normalized strength recovery degree.
[0129] Furthermore, relevant experiments were conducted using the method of the present application, taking the self-healing experiment of concrete with different amounts of calcium nitrate, sodium silicate and crystalline admixture Xypex as an example to illustrate the method of the present application.
[0130] 1. Experimental preparation and data collection.
[0131] In this test, CEM 52.5N Portland cement was used as the main binder, and 20% of the cement was replaced by slag powder. The maximum particle size of the coarse aggregate was 10 mm, and river sand was used as the fine aggregate. The water-cement ratio was set to 0.39, and a high-efficiency water reducer was used to maintain the consistency within 150 ± 30 mm. Except for the high-efficiency water reducer, no other admixtures were added to the reference concrete (Ref). Concrete in the other test groups was prepared according to the mix design in Table 1, with the addition of different admixtures: calcium nitrate (CN-2, CN-3, CN-4, CN-6), water glass (SS-2, SS-4) and crystallizing admixtures (CA-3, CA-4, CA-6).
[0132] According to the mix ratio in Table 1, 10 groups of 100 mm cubic test specimens were cast. The concrete specimens in each test specimen group were demoulded one day after casting and cured for 28 days in a curing room at a temperature of 28°C ± 2 and a humidity of 100%. After the curing, the performance of the concrete specimens was tested.
[0133] Table 1 Concrete test mix ratio
[0134]
[0135] First, the crack width healing test was conducted on the precast cracked concrete specimens. The precast cracked concrete specimens after curing for 28 days were loaded at a speed of 0.01mm / min to 0.05mm / min on a uniaxial hydraulic press to induce cracks of 150μm±50μm. The positions of 3 or more cracks on the precast cracked concrete specimens were calibrated using an electron microscope and recorded as the initial test value of the crack width of the precast cracked concrete specimens.
[0136] After the initial crack width healing test of the prefabricated cracked concrete specimens, the water absorption performance test of the prefabricated cracked concrete specimens and the non-prefabricated cracked concrete specimens was immediately carried out. The upper and lower surfaces of the two groups of 100mm cubic specimens were first polished smooth, placed in a 50℃ oven for 3 days, and then taken out and placed in a container at 28℃ for drying and curing for 15 days. Then, the sides of the specimens were sealed with epoxy resin, and the top surface was covered with plastic film, so that the bottom of the specimens were exposed to water within 2±1mm. The degree of change in water absorption of different specimen groups was then measured.
[0137] After the water absorption performance test of the two groups of samples was completed, all concrete samples were placed in a water immersion environment for continued curing and healing, and the crack healing conditions of the same positions of the prefabricated cracked concrete samples were observed and recorded every week until the new healing period of 28 days was over.
[0138] After the healing period, the crack width of the precast cracked concrete specimens was tested for the second time according to the above operation. After the second crack width test, the concrete specimens of the precast cracked concrete specimens and the non-precast cracked concrete specimens were tested for water absorption performance in the same way as the above operation, and the degree of change in water absorption of different specimen groups was measured. Subsequently, the strength recovery test of the precast cracked concrete specimens was carried out.
[0139] When conducting the concrete strength recovery test, a uniaxial hydraulic press was used to load at a speed of 0.01 mm / min to 0.05 mm / min until the existing crack in the middle of the specimen expanded to about 300 μm ± 50 μm. The load when the prefabricated crack reached the target width was used to determine the strength recovery of the concrete specimen. The experimental data obtained after the performance test are shown in Table 2.
[0140] Table 2 Test value table
[0141]
[0142] 2. Data normalization processing.
[0143] The normalized water absorption rate change, the normalized crack width change and the normalized strength recovery are shown in Figure 2 shown. Figure 2 In the figure, the larger the values of the normalized water absorption rate change, the normalized crack width change, and the normalized strength recovery, the closer they are to 1, indicating that the performance recovery degree of this group of samples is higher and the self-healing performance is stronger.
[0144] 3. To comprehensively analyze the performance characteristics of water absorption recovery and crack width recovery, the correlation coefficient is calculated based on the normalized water absorption change, the normalized crack width change and the normalized strength recovery, and the following is plotted: Figure 3 The correlation coefficient heat map is shown. Taking the strength recovery degree as a reference, the water absorption recovery weight α and the crack width healing weight β are calculated, α = 0.63, β = 0.37. The water absorption recovery weight and the crack width healing weight are quite different, with a gap of nearly double. The water absorption recovery weight is larger, indicating that the degree of healing and repair of the internal crack damage of the concrete is higher.
[0145] 4. The weighted water absorption change degree is determined based on the normalized water absorption change degree and the water absorption recovery weight, and the weighted crack width change degree is determined based on the normalized crack width change degree and the crack width healing weight. The TOPSIS comprehensive analysis method is used to determine the similarity coefficient of each sample group based on the weighted water absorption change degree and the weighted crack width change degree of all sample groups. Finally, the similarity coefficient is used as the TOPSIS score to sort them. The closer the TOPSIS score is to 1, the better the self-healing performance of the sample group. The results are shown in Table 3. As can be seen from Table 3, CN-6 has the highest score based on TOPSIS analysis, with a score of 1, and its self-healing performance is much better than that of concrete under other environmental conditions. Compared with the ordinary concrete in the control group, the internal and external self-healing performance of CN-6 has increased by more than 3 times in the comprehensive score.
[0146] Table 3 TOPSIS scores and rankings
[0147] Positive ideal distance Negative ideal distance TOPSIS score Ranking Ref 0.635 0.292 0.315 8 CN-2 0.558 0.269 0.325 6 CN-3 0.365 0.369 0.502 3 CN-4 0.634 0.299 0.320 7 CN-6 0 0.731 1 1 SS-2 0.474 0.334 0.413 4 SS-4 0.454 0.278 0.380 5 CA-3 0.563 0.249 0.307 9 CA-4 0.224 0.513 0.696 2 CA-6 0.666 0.068 0.092 10
[0148] 5. To verify the accuracy of the above analysis, the Bland-Altman method was used to compare and analyze the relationship between the TOPSIS score and the normalized strength recovery degree. The results are shown in the figure below. Figure 4 As shown. Figure 4 It can be seen that the average difference between the TOPSIS comprehensive score and the normalized strength recovery degree is -0.39, indicating that the TOPSIS score is slightly lower than the normalized strength recovery degree, and there is no obvious systematic deviation between the two as a whole. The data consistency limits are 0.48 and -1.26. Except for one data point that is very close to the lower limit, the remaining points are between the upper and lower limits, indicating that the difference between the TOPSIS score and the normalized strength recovery degree is not serious. This shows that there is a good consistency between the comprehensive score of concrete self-healing ability based on TOPSIS and the normalized strength recovery degree, and also reflects that the method of this application is more accurate.
[0149] In an exemplary embodiment, a computer device is provided, including: a memory, a processor, and a computer program stored in the memory and executable on the processor, wherein the processor executes the computer program to implement a method for determining preparation parameters using a TOPSIS-based concrete self-healing performance evaluation technique.
[0150] In an exemplary embodiment, a computer-readable storage medium is provided, on which a computer program is stored. When the computer program is executed by a processor, a method for determining preparation parameters using a concrete self-healing performance evaluation technology based on TOPSIS is implemented.
[0151] In an exemplary embodiment, a computer program product is provided, including a computer program, which, when executed by a processor, implements a method for determining preparation parameters using a concrete self-healing performance evaluation technique based on TOPSIS.
[0152] In an exemplary embodiment, a computer device is provided. The computer device may be a server or a terminal. The internal structure diagram thereof may be as follows: Figure 5 As shown. The computer device includes a processor, a memory, an input / output interface (Input / Output, referred to as I / O) and a communication interface. The processor, the memory and the input / output interface are connected through a system bus, and the communication interface is connected to the system bus through the input / output interface. The processor of the computer device is used to provide computing and control capabilities. The memory of the computer device includes a non-volatile storage medium and an internal memory. The non-volatile storage medium stores an operating system, a computer program and a database. The internal memory provides an environment for the operation of the operating system and the computer program in the non-volatile storage medium. The input / output interface of the computer device is used to exchange information between the processor and an external device. The communication interface of the computer device is used to communicate with an external terminal through a network connection. When the computer program is executed by the processor, a method for determining preparation parameters using a concrete self-healing performance evaluation technology based on TOPSIS is implemented.
[0153] Those skilled in the art will understand that Figure 5 The structure shown in the figure is only a block diagram of a part of the structure related to the solution of the present application, and does not constitute a limitation on the computer device to which the solution of the present application is applied. The specific computer device may include more or fewer components than those shown in the figure, or combine certain components, or have a different arrangement of components.
[0154] It should be noted that the user information (including but not limited to user device information, user personal information, etc.) and data (including but not limited to data used for analysis, stored data, displayed data, etc.) involved in this application are all information and data authorized by the user or fully authorized by all parties, and the collection, use and processing of relevant data must comply with relevant regulations.
[0155] Those of ordinary skill in the art can understand that all or part of the processes in the above-mentioned embodiment methods can be completed by instructing the relevant hardware through a computer program, and the computer program can be stored in a non-volatile computer-readable storage medium. When the computer program is executed, it can include the processes of the embodiments of the above-mentioned methods. Among them, any reference to the memory, database or other medium used in the embodiments provided in the present application can include at least one of non-volatile and volatile memory. Non-volatile memory can include read-only memory (ROM), magnetic tape, floppy disk, flash memory, optical memory, high-density embedded non-volatile memory, resistive random access memory (ReRAM), magnetic random access memory (MRAM), ferroelectric random access memory (FRAM), phase change memory (PCM), graphene memory, etc. Volatile memory can include random access memory (RAM) or external cache memory, etc. By way of illustration and not limitation, RAM may be in various forms, such as static random access memory (SRAM) or dynamic random access memory (DRAM).
[0156] The database involved in each embodiment provided in this application may include at least one of a relational database and a non-relational database. The non-relational database may include a distributed database based on blockchain, etc., but is not limited thereto. The processor involved in each embodiment provided in this application may be a general-purpose processor, a central processing unit, a graphics processor, a digital signal processor, a programmable logic device, a data processing logic device based on quantum computing, etc., but is not limited thereto.
[0157] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0158] This article uses specific examples to illustrate the principles and implementation methods of this application. The above examples are only to help understand the method and core ideas of this application. For those skilled in the art, according to the ideas of this application, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as limiting this application.
Claims
1. A method for determining preparation parameters using TOPSIS-based concrete self-healing performance evaluation technology, characterized in that: The method for determining preparation parameters using the concrete self-healing performance evaluation technology based on TOPSIS includes: Prepare multiple groups of sample groups; the sample groups include: prefabricated cracked concrete samples and non-prefabricated cracked concrete samples; the prefabricated cracked concrete samples are concrete samples with cracks, and the non-prefabricated cracked concrete samples are concrete samples without cracks; the preparation parameters of the concrete samples in different groups of sample groups are different, and the preparation parameters of the prefabricated cracked concrete samples and the non-prefabricated cracked concrete samples in the same group are the same; the preparation parameters include: the types of materials constituting the concrete samples and the mix ratio of the materials; Performing performance tests on each of the sample groups respectively, and obtaining the normalized water absorption rate change degree, the normalized crack width change degree, and the normalized strength recovery degree of each of the sample groups; Based on the normalized water absorption change degree, the normalized crack width change degree and the normalized strength recovery degree of all sample groups, the water absorption recovery weight and the crack width healing weight are determined; Determine the weighted water absorption change degree of each sample group based on the normalized water absorption change degree of each sample group and the water absorption recovery weight, and determine the weighted crack width change degree of each sample group based on the normalized crack width change degree of each sample group and the crack width healing weight; Using the TOPSIS comprehensive analysis method, based on the weighted water absorption rate change degree and the weighted crack width change degree of all sample groups, the similarity coefficient of each sample group is determined; the similarity coefficient is used to characterize the self-healing performance; The preparation parameters of the sample group with the largest similarity coefficient are determined as target parameters, and the target parameters are determined as preparation parameters when producing concrete.
2. The method for determining preparation parameters using TOPSIS-based concrete self-healing performance evaluation technology according to claim 1, characterized in that: The performance tests are performed on each sample group respectively, and the normalized water absorption rate change degree, the normalized crack width change degree and the normalized strength recovery degree of each sample group are obtained, including: The precast cracked concrete specimens in each specimen group are respectively subjected to performance tests. During the performance tests, the performance parameters of each precast cracked concrete specimen are collected. The performance parameters of the precast cracked concrete specimens include: a first load, a first crack width, a first water absorption rate, a second crack width, a second water absorption rate, and a second load. The non-prefabricated cracked concrete samples in each sample group are respectively subjected to performance tests. During the performance tests, the performance parameters of each non-prefabricated cracked concrete sample are collected. The performance parameters of the non-prefabricated cracked concrete sample include: the third water absorption rate and the fourth water absorption rate; Calculating the change degree of the original water absorption of each sample group according to the first water absorption, the second water absorption, the third water absorption and the fourth water absorption in each sample group, and performing maximum and minimum normalization processing on the change degree of the original water absorption of each sample group to obtain the normalized change degree of water absorption of each sample group; Calculating the change degree of the original crack width of each sample group according to the first crack width and the second crack width in each sample group, and performing maximum and minimum normalization processing on the change degree of the original crack width of each sample group to obtain the normalized change degree of the crack width of each sample group; The original strength recovery degree of each sample group is calculated according to the first load and the second load in each sample group, and the original strength recovery degree of each sample group is normalized to the maximum and minimum to obtain the normalized strength recovery degree of each sample group.
3. The method for determining preparation parameters using TOPSIS-based concrete self-healing performance evaluation technology according to claim 2, characterized in that: The calculation formula for the change in the original water absorption rate includes: Δw=(w1-w2)-(w3-w4); Among them, Δw is the degree of change of the original water absorption rate; w1 is the first water absorption rate; w2 is the second water absorption rate; w3 is the third water absorption rate; w4 is the fourth water absorption rate.
4. The method for determining preparation parameters using TOPSIS-based concrete self-healing performance evaluation technology according to claim 2, characterized in that: The calculation formula for the change in the original crack width includes: Among them, Δc is the change degree of the original crack width; c1 is the first crack width; c2 is the second crack width.
5. The method for determining preparation parameters using TOPSIS-based concrete self-healing performance evaluation technology according to claim 1, characterized in that: Based on the normalized water absorption change degree, normalized crack width change degree and normalized strength recovery degree of all sample groups, the water absorption recovery weight and crack width healing weight are determined, including: Based on the normalized water absorption change degree and the normalized strength recovery degree of all sample groups, the correlation coefficient between the water absorption change degree and the strength recovery degree is calculated to obtain the water absorption recovery correlation coefficient; Based on the normalized crack width change degree and the normalized strength recovery degree of all sample groups, the correlation coefficient between the crack width change degree and the strength recovery degree is calculated to obtain the crack width healing correlation coefficient; Based on the water absorption recovery correlation coefficient and the crack width healing correlation coefficient, the water absorption recovery weight and the crack width healing weight are calculated.
6. The method for determining preparation parameters using TOPSIS-based concrete self-healing performance evaluation technology according to claim 1, characterized in that: Using the TOPSIS comprehensive analysis method, based on the weighted water absorption rate change degree and weighted crack width change degree of all sample groups, the similarity coefficient of each sample group is determined, including: The maximum value among all weighted water absorption rate changes is determined as the positive ideal solution of water absorption rate, the minimum value among all weighted water absorption rate changes is determined as the negative ideal solution of water absorption rate, the maximum value among all weighted crack width changes is determined as the positive ideal solution of crack width, and the minimum value among all weighted crack width changes is determined as the negative ideal solution of crack width; The similarity coefficient of each sample group is determined according to the weighted water absorption change degree and the weighted crack width change degree of each sample group and the positive ideal solution of water absorption, the negative ideal solution of water absorption, the positive ideal solution of crack width and the negative ideal solution of crack width.
7. The method for determining preparation parameters using TOPSIS-based concrete self-healing performance evaluation technology according to claim 6, characterized in that: The similarity coefficient of each sample group is determined according to the weighted water absorption change degree and the weighted crack width change degree of each sample group and the positive ideal solution of water absorption, the negative ideal solution of water absorption, the positive ideal solution of crack width and the negative ideal solution of crack width, including: Determine any sample group as the current sample group; Calculating the positive ideal distance of the current sample group according to the positive ideal solution of water absorption, the positive ideal solution of crack width, and the weighted degree of change of water absorption and the weighted degree of change of crack width of the current sample group; Calculating the negative ideal distance of the current sample group according to the negative ideal solution of water absorption, the negative ideal solution of crack width, and the weighted degree of change of water absorption and the weighted degree of change of crack width of the current sample group; The similarity coefficient of the current sample group is calculated according to the positive ideal distance and the negative ideal distance of the current sample group.
8. A computer device comprising: A memory, a processor, and a computer program stored in the memory and executable on the processor, wherein the processor executes the computer program to implement the method for determining preparation parameters using TOPSIS-based concrete self-healing performance evaluation technology as described in any one of claims 1 to 7.
9. A computer-readable storage medium having a computer program stored thereon, characterized in that: When the computer program is executed by a processor, the method for determining preparation parameters by using the concrete self-healing performance evaluation technology based on TOPSIS as described in any one of claims 1 to 7 is implemented.
10. A computer program product, comprising a computer program, characterized in that When the computer program is executed by a processor, the method for determining preparation parameters by using the concrete self-healing performance evaluation technology based on TOPSIS as described in any one of claims 1 to 7 is implemented.
Citation Information
Patent Citations
Self-healing concrete crack repair inspection method
CN114577563A
Self-healing concrete compression damage healing evaluation method
CN116930466A
Diagnostic strip cutting apparatus with selection and separation discharge
KR1020200109613A